Effects of tear size on outcomes after acellular dermal matrix-augmented rotator cuff repair - Park, Ji-Hun; Kim, Jung-Han; Koo, Hyung-Jun (Clinics in shoulder and elbow, 2025)
Acellular dermal matrix (ADM) patch augmentation in rotator cuff repair reinforces the repaired tendon and provides additional structural support. This study aimed to compare outcomes based on rotator cuff tear size. We retrospectively reviewed patients who underwent ADM-augmented rotator cuff repair at two hospitals between April 2021 and April 2023. After excluding subjects with <2 years of follow-up or no magnetic resonance imaging (MRI) at 6 months, patients were grouped based on tear size: ≤30 mm (group 1) and >30 mm (group 2). Outcomes were American Shoulder and Elbow Surgeons score, Constant-Murley score, University of California, Los Angeles score, pain visual analog scale score, and range of motion (ROM). Retear was defined based on Sugaya type 4-5 on 6-month MRI. Both groups showed significant improvement in postoperative clinical outcomes compared with preoperative outcomes, with no significant intergroup differences. ROM gains were limited overall, with significant increases only in group 1 for forward flexion and scaption. Stiffness occurred in 4.8% of group 1 and 17.9% of group 2 patients. Retear was found in 1 of 21 patients (4.8%) in group 1 and 7 of 28 (25.0%) in group 2. Arthroscopic rotator cuff repair with ADM patch augmentation showed reduced retear rates and improved clinical outcomes across tear sizes. Postoperative ROM improvements were limited, and stiffness tended to occur more frequently in larger tears. Thus, the success of ADM patch augmentation depends on patient selection and appropriate graft application. Level of evidence: III.